2018
DOI: 10.1016/j.ijsu.2018.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel release with a new mini-incision approach versus a conventional approach, a retrospective cohort study

Abstract: Patients with mini-incision approach have satisfactory surgical outcomes, low postoperative complications, and good appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
6
20
0
4
Order By: Relevance
“…The main complaint of the patients was about the scar of the surgery and the date of starting to use their hand in daily activities and return to work. 5,6,9,11,14,15,[18][19][20] Therefore, the later points were of interest for clinical analysis of the results of this study. The differences between both groups were statistically significant regarding the operative data.…”
Section: Resultsmentioning
confidence: 99%
“…The main complaint of the patients was about the scar of the surgery and the date of starting to use their hand in daily activities and return to work. 5,6,9,11,14,15,[18][19][20] Therefore, the later points were of interest for clinical analysis of the results of this study. The differences between both groups were statistically significant regarding the operative data.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical treatment should be performed in unresponsive patients [2,3,8]. The patients who are operated with a classical longitudinal incision (incision starting proximal to the superficial palmar arch, immediately followed by turning the wrist line at an angle of 45 degrees towards the ulnar side and passing the wrist line about 1cm) cannot use their hands for about 15 days due to postoperative pain, limitation of movement and scar tissue [6]. For these reasons, minimal approaches have been introduced in recent years in order to replace this surgical method [7].…”
Section: Discussionmentioning
confidence: 99%
“… 15 16) There are abundant reports on grip strength recovery patterns following CTR, and most researchers have suggested that patients usually achieved total grip strength recovery 3 to 6 months postoperatively ( Table 1 ). 2 17 18 19 20 21 22 23 24 25 26 27) Some researchers reported rapid grip strength recovery in 4 to 6 weeks postoperatively. 2 17 19 23) …”
Section: Grip Strength In Carpal Tunnel Syndromementioning
confidence: 99%